APPROACHING MOTHER-TONGUE EDUCATION AS A PERSONAL AND SOCIETAL DEVELOPMENT STRATEGY (The University of Nairobi Journal of Language and Linguistics, 2023)
This paper underscores the need for a broadly defined market orientation in ouradvocacy for mother-tongue learning, as well as in the research that seeks toestablish the value of mother-tongue competence in Africa. The paper callsattention to the fact that the world of today is driven by market ethics, in whichpeople‟s choices are guided by the persistent quest for what to sell in themarket of opportunities, both in the social and material domains of life. Ouryoung people must be shown how speaking a mother-tongue opens upopportunities for self-advancement in their struggles to make life meaningful.This general argument is hinged on literature from both linguistic and nonlinguistic scholarship, and illustrated with Kenya‟s sociolinguistic realities andthe corresponding constitutional and policy provisions.